Do Auditor Firm Size and Financial Expertise of Audit Committee Affect Voluntary Disclosure of Nigerian Banks? - Hussein Omeiza Umaru; Olawale Bunmi; Umaru Usman Ozovehe; Adamu Mohammed Shalli (Universitas Syiah Kuala, 2021)
Objective – This study explores the effect of auditor firm size and audit committee financial expertise on voluntary disclosure of Nigerian listed banks. Design/methodology – The correlational research design is adopted. The secondary data source was obtained from the audited annual financial statement of the banks from 2008 to 2018. The study sample size is 13 listed banks drawn out of a population of 15 Nigerian listed banks as reflected in the Nigerian Stock Exchange (NSE) fact book as at 31st December, 2018. The study employed the robust ordinary least square (OLS) regression technique to analyze the panel data obtained for the study. Results – The finding reveals that auditor firm size has a significant positive effect with voluntary disclosure of Nigeria banks. Similarly, financial expertise of audit committee has a significant positive effect on voluntary disclosure of the banks in Nigeria. The result suggest that the choice of big audit firms by clients, regulators and users of audited financial statement against their counterparts (non-big four) is warranted. The management should ensure that the audit committee members with accounting and finance expertise possess requisite knowledge of the industry. Originality – Extant studies are foreign based. However, findings from such studies may not be applicable in Nigeria due to different requirements, given environmental disparities amongst others.